Identification of BCMV resistant germplasm in mungbean (Vigna radiata) using serological and molecular diagnostics - DEEPIKA, D D; TRIPATHI, KULDEEP; J, ABHISHEK G; SINGH, NEETA; SHARMA, RUCHI; SHARMA, VAISHALI DUTTA; MAURYA, A K; CHALAM, V CELIA (The Indian Journal of Agricultural Sciences, 2023)
Diverse germplasm of mungbean serves as a source of resistant gene, screening of germplasm for BCMV resistance will provide resistance source. So, in 2018–2019 a total of 65 diverse mungbean accessions along with susceptible and resistant checks were screened against BCMV under natural conditions in the field and artificial inoculation under controlled conditions. Transmission electron microscopy, per cent disease incidence, serological Direct antigen coating- Enzyme-linked immunosorbent assay (DAC-ELISA) and reverse transcription-polymerase chain reaction (RT-PCR) diagnostics were used to detect and identify the BCMV resistant accessions. The study revealed that a total of 29 accessions were found to be immune to BCMV infections. However, these accessions need to be further evaluated in BCMV disease hotspots and under multilocation trials. Therefore, in the present study, accessions that were immune to BCMV may serve as valuable donors for the BCMV resistant mungbean breeding programme.